2018
DOI: 10.1101/345900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downregulation of the central noradrenergic system by Toxoplasma gondii infection

Abstract: 26The parasitic protozoan Toxoplasma gondii becomes encysted in brain and muscle tissue 27 during chronic infection, a stage that was previously thought to be dormant but has been 28 found to be active and associated with physiological effects in the host. Dysregulation of 29 catecholamines in the CNS has previously been observed in chronically-infected animals. In 30 the study described here, the noradrenergic system was suppressed with decreased levels of 31 norepinephrine in brains of infected animals and i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 79 publications
(112 reference statements)
3
51
0
Order By: Relevance
“…Future experiments will further investigate this novel induced lncRNA. hence, the widespread DBH down-regulation provides an explanation for changes in noradrenergic-linked behaviours in chronically-infected mice (13,52). We propose a model of T. gondii inducing host-encoded lncRNAs that are packaged and released from host neuronal cells during chronic infection to modulate the host environment; extending studies that found T. gondii-infected fibroblasts and macrophages can induce host lncRNAs (53).…”
Section: Evs From Infected Cells Contain An Antisense Dbh Lncrnasupporting
confidence: 54%
See 1 more Smart Citation
“…Future experiments will further investigate this novel induced lncRNA. hence, the widespread DBH down-regulation provides an explanation for changes in noradrenergic-linked behaviours in chronically-infected mice (13,52). We propose a model of T. gondii inducing host-encoded lncRNAs that are packaged and released from host neuronal cells during chronic infection to modulate the host environment; extending studies that found T. gondii-infected fibroblasts and macrophages can induce host lncRNAs (53).…”
Section: Evs From Infected Cells Contain An Antisense Dbh Lncrnasupporting
confidence: 54%
“…(4)(5)(6). The changes are associated with neurotransmitter modifications and neuroinflammation although the mechanisms responsible are poorly understood (7)(8)(9)(10)(11)(12)(13). Seropositivity in humans ranges from 10-90% in different parts of the world with >40m people in the USA carrying the parasite (DPDx, Centers for Disease Control, USA).…”
Section: Introductionmentioning
confidence: 99%
“…This explains the observation of high-concentration tissue cysts in the amygdala and nucleus accumbens, containing dopamine in limbic regions of the brain known to be an important control of motivation, pleasure, dependence, reward, and fear [47]. Other effects are more intriguing; Alteration of the neurotransmitter involves the production of homologous proteins to aromatic amino acid TH and dopamine (DOPA) 2 receptor (D2R) compounds with an increase in DOPA synthesis, tryptophan (TRP) degradation and the decrease in serotonin synthesis [56,65].…”
Section: The Neurobiological Studies Related To T G O N D I I Infectmentioning
confidence: 99%
“…In addition to an inflammatory response, T. gondii infection causes several neurochemical changes including glutamate and dopamine dysregulation [189,190]. During chronic infection with T. gondii, the astrocytic glutamate transporter GLT-1 is reportedly reduced in the forebrain over time, leading to increases in extracellular glutamate and excitotoxicity [189].…”
Section: Chronic Stagementioning
confidence: 99%